Pengaruh Implementasi Model Pembelajaran Two Stay Two Stray Terhadap Motivasi Belajar Siswa dan Penguasaan Konsep Sistem Pernapasan Manusia (Di Kelas VIII SMP Miftahul Falah Kabupaten Kuningan) - Yudhia Prawira, Mochammad Yusup; Nur, Sofyan Hasanuddin; Arif, Asep Ginanjar (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2022)
The problem that is the focus of this research is the decline in students' learning motivation and the ability to master concepts in class VIII students in science subjects at Miftahul Falah Middle School, Kuningan Regency. The objectives of the research carried out were: 1) Analyzing the effect of implementing the Two Stay Two Stray learning model on student learning motivation; 2) Analyzing the effect of implementing the Two Stay Two Stray learning model on Mastery of Human Respiratory System Concepts; 3) Analyze the differences in Mastery of Human Respiratory System Concepts in classes that apply the Two Stay Two Stray learning model (experimental class) and classes that apply the expository model (control class); 4) Knowing students' responses to the implementation of the Two Stay Two Stray learning model in class VIII of Miftahul Falah Middle School, Kuningan Regency; The method used in this research is a quasi-experimental method. The subjects in this research were 52 Class VIII students of Miftahul Fallah Middle School, Kuningan Regency, consisting of class VIII.A (26 people) as the experimental class and class VIII. B (26 people) as the control class. Based on the results of calculations and data analysis, it can be concluded that: 1) There is an influence of the implementation of the Two Stay Two Stray learning model on student learning motivation; 2) There is an influence of the implementation of the Two Stay Two Stray learning model on Concept Mastery; 3) There is a difference in Mastery of Human Respiratory System Concepts in classes that apply the Two Stay Two Stray learning model (experimental class) and classes that apply the expository model (control class); 4) Students have a positive response to science learning by implementing the Two Stay Two Stray learning model, the result of the student response percentage is 81.32% who give positive responses and are interested in using the Two Stay Two Stray learning model.